2011
DOI: 10.1080/01446193.2011.610330
|View full text |Cite
|
Sign up to set email alerts
|

Modelling profitability and effectiveness of Greek-listed construction firms: an integrated DEA and ratio analysis

Abstract: Existing research on construction performance measurement is dominated by project level studies, and the firm stakeholders require the development of models that compare performance in terms of efficiency. A new framework that integrates data envelopment analysis (DEA) and ratio analysis using a two-step approach is described to evaluate performance in terms of profitability and effectiveness of a sample of construction firms listed on the Athens Exchange. In the first step, profitability and effectiveness are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…Furthermore, to the best of our knowledge, this study is the first to estimate the TE of the Spanish construction sector using SFA. This research found, as its main conclusion, that the average Technical Efficiency of the Spanish construction sector is 0.85 in the period 1996-2011. From 2003 to 2011 the sector TE shows a steady decrease of some 8 % in total.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Furthermore, to the best of our knowledge, this study is the first to estimate the TE of the Spanish construction sector using SFA. This research found, as its main conclusion, that the average Technical Efficiency of the Spanish construction sector is 0.85 in the period 1996-2011. From 2003 to 2011 the sector TE shows a steady decrease of some 8 % in total.…”
Section: Resultsmentioning
confidence: 62%
“…There are very few studies analysing the efficiency of the construction sector and, to the best of our knowledge, there is just one, You and Zi (2007), approximating the effect of an economic crisis on the efficiency of the construction industry. Globally, country studies focused on the whole construction sector, report a wide range of efficiency levels from a low of around 50% for Canadian firms (Pilateris and McCabe, 2003), approximately 60% for Portuguese firms (Horta, Camanho and Moreira da Costa, 2012), to higher estimates of 83% for Norwegian firms (Edvardsen, 2004), 84% for Chinese firms (Zheng, Chau and Hui, 2011) and 93% for Greek firms (Tsolas, 2011).…”
Section: Efficiency Crisis and The Construction Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…2015). Other important studies were developed in Italy, Greece, Portugal, and Jordan (Guerrini et al, 2013); (Tsolas, 2011); (Horta et al, 2010); (El-Mashaleh et al, 2006).…”
Section: Dea In the Construction Industrymentioning
confidence: 99%
“…Previous studies of the construction sector have analyzed inefficiency measures for all inputs employed simultaneously, without distinguishing the contribution of each input to overall firms' performance. Those relate to construction companies in Spain (Kapelko et al 2014;Kapelko and Oude Lansink 2015a), Portugal (Horta et al 2012), Iran (Wong et al 2012), Canada (Pilateris and McCabe 2003), Greece (Tsolas 2011), Footnote 2 continued context by Kapelko and Oude Lansink (2017) with application to the measurement of input-specific dynamic inefficiency of European dairy manufacturing firms. 3 There is also an important stream of research that analyzes the input-specific productivity evolution over time; this includes Mahlberg andSahoo (2011), Chang et al (2012) and Kapelko et al (2015b).…”
Section: Introductionmentioning
confidence: 99%